Role of Renin–Angiotensin System and Macrophages in Breast Cancer Microenvironment - Abir Abdullah Alamro; Moudhi Abdullah Almutlaq; Amani Ahmed Alghamdi; Atekah Hazzaa Alshammari; Eman Alshehri; Saba Abdi (Diseases)
Background/Objectives: The renin–angiotensin system (RAS) is well-established as a moderator of cardiovascular equilibrium and blood pressure. Nevertheless, growing evidence indicates that angiotensin II (Ang II), the principal RAS effector peptide, together with additional constituents, is involved in various malignancies. Since the immune system is an important aspect in tumor development, this study sought to investigate the role of Ang II in the crosstalk between tumor-associated macrophages (TAMs) and breast cancer cells in the tumor microenvironment (TME). Methods: We treated THP-1-like macrophages with 100 nM Ang II for 24 h. The culture media thus obtained was used as conditioned media and applied at 50% on MCF-7 and MDA-MB-231 breast cancer cell lines. The effects of the conditioned media on cancer cell lines were then investigated by various methods such as a cell proliferation assay, migration assay, polarization assay, and by the detection of apoptosis and reactive oxygen species (ROS) generation. Results: We demonstrated that in vitro Ang II promotes macrophage polarization toward proinflammatory M1-like macrophages and anti-inflammatory M2-like macrophages. Interestingly, Ang II, through macrophages, showed varied effects on different breast cancer cell lines, promoting tumor growth and progression in MCF-7 while inhibiting tumor growth and progression in MDA-MB-23. Conclusions: This study has provided clear evidence that Ang II in the TME modulates TAM polarization and secretions, leading to different effects based on the type of breast cancer.